Dead time control signal for non-isolated synchronous buck DC-DC converter - Hariri, Muhammad Hafeez Mohamed; Daud, Noor Dzulaikha; Sutikno, Tole; Yusoff, Nor Azizah Mohd; Desa, Mohd Khairunaz Mat (Institute of Advanced Engineering and Science, 2025)
This study introduces a simple dead-time control signal for the non-isolated synchronous buck DC-DC converter, incorporated alongside maximum power point tracking (MPPT) for a stand-alone photovoltaic (PV) system. Dead-time control in non-isolated DC-DC converters is challenging due to difficulties in accurately sensing and predicting errors, especially during the transition between switching modes. The introduction of the dead-time control method resulted in optimal efficiency for the stand-alone PV system. The dead-time control was implemented in the hardware prototype using a bootstrap technique. Power generation from the PV module was optimized through the DC converter's implementation of an improved perturb and observe (P&O) MPPT approach. According to the results, the proposed design achieved an overall system efficiency of 80%. Moreover, the enhanced P&O MPPT algorithm prototype was observed to produce a maximum output power of 60 W.